Decitabine bioproduction using a biocatalyst with improved stability by adding nanocomposites - Mendez, Mariana Beatriz (2020)
A novel IDA-LaNDT derivative was able to reach the highest productivity in the biosynthesis of a well-known antitumoral agent called decitabine. However, the combination of two simple and inexpensive techniques such as ionic absorption and gel entrapment with the incorporation of a bionanocomposite such as bentonite significantly improved the stability of this biocatalyst. These modifications allowed the enhancement of storage stability (for at least 18 months), reusability (400 h of successive batches without significant loss of its initial activity), and thermal and solvent stability with respect to the non-entrapped derivative. Moreover, reaction conditions were optimized by increasing the solubility of 5-aza by dilution with dimethylsulfoxide. Therefore, a scale-up of the bioprocess was assayed using the developed biocatalyst, obtaining 221 mg/L·h of DAC. Finally, green parameters were calculated using the nanostabilized biocatalyst, whose results indicated that it was able to biosynthesize DAC by a smooth, cheap, and environmentally friendly methodology.